The Role of Innovative Ecotourism Development Competency in Improving the Marketing Performance - Simanjuntak, Mariana; Situmeang, Frederik (Universitas Muria Kudus, 2025)
This study examines the influence of a nature-based environment on innovation capability and entrepreneurial sustainability in three districts and the factors influencing the competitive advantage of Indonesian Lake Toba ecotourism. SEM was used to test the hypotheses. The 197 respondents were ecotourism-SMEs entrepreneurs, capital owners, community leaders, and government. Responsive-market orientation exhibits the most decisive influence on IEDC. Competitive advantage begins with comprehensive entrepreneurial innovation activities, including product and process innovation and activities related to marketing. Factors that influence the sustainability of ecotourism in Lake Toba, cannot be separated from the presence of management that prioritizes holistic entrepreneurial products and services including the availability of food stalls, strengthening local access and transportation, shopping places, accommodation, ecotourism tours, and entertainment that reflect the dynamics of services to improve ecotourism marketing performance. This study explores the extent to which ecotourism-industry entrepreneurs possess a responsive market orientation by focusing on the role of current market experiences in generating innovative and proactive ideas for the development of market sustainability. People communities around ecotourism destinations may gain benefits by capturing the opportunities of ecotourism.